2011
DOI: 10.1080/13670051003657959
|View full text |Cite
|
Sign up to set email alerts
|

Cross-language transfer of spelling strategies in English and Afrikaans Grade 3 children

Abstract: This study examined strategies for spelling accuracy in Grade 3 children. Thirty bilingual, AfrikaansÁEnglish speaking children and 30 monolingual, Englishspeaking children were assessed on their ability to spell English words and nonwords. The bilingual children were also assessed on their Afrikaans word and non-word spelling abilities. In terms of spelling accuracy, the monolingual children had significantly higher scores for the complex opaque English words and non-words than did the bilingual children. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…grapheme association rules, and graphemes may represent a number of different phonemes, for example, the English writing system consists of several ways to pronounce the same grapheme, for example, the a in: start /ɑ:/, call /ɔ:/, cat /ae/, care /eә/ and another /ә/ (De Sousa et al 2011). In transparent orthographies, such as Afrikaans, the phonemegrapheme association rules are reliable, and graphemes mostly symbolise only one phoneme (De Sousa et al 2011;Tibi & Kirby 2018).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…grapheme association rules, and graphemes may represent a number of different phonemes, for example, the English writing system consists of several ways to pronounce the same grapheme, for example, the a in: start /ɑ:/, call /ɔ:/, cat /ae/, care /eә/ and another /ә/ (De Sousa et al 2011). In transparent orthographies, such as Afrikaans, the phonemegrapheme association rules are reliable, and graphemes mostly symbolise only one phoneme (De Sousa et al 2011;Tibi & Kirby 2018).…”
Section: Figurementioning
confidence: 99%
“…Alphabetic orthographies -or writing systems -are all created on the principles of phoneme-grapheme association (Vibulpatanavong & Evans 2019). The orthography of a language is described as being either transparent or opaque (De Sousa, Greenop & Jessica 2011). Opaque orthographies present with inconsistent and unpredictable phoneme-…”
Section: Introductionmentioning
confidence: 99%
“…There are schools in which children are taught to read in Afrikaans (an orthographically transparent language) and schools in which reading is taught in English (an orthographically opaque language). De Sousa et al [53] Training Reading, Writing and Spelling Fluency: Centre-Periphery Dissemination… DOI: http://dx.doi.org /10.5772/intechopen.82812 reported that bilingual English-and Afrikaans-speaking children showed greater spelling accuracy in the spelling of Afrikaans words and non-words compared to their spelling of English words and non-words. The bilingual children's ability to spell in Afrikaans and English was correlated, signifying a cross-language relationship for spelling both languages, but with language background and orthographic depth exerting an influence on the nature and development of spelling strategies used to spell in an orthographically different first language and second language.…”
Section: Transparent Versus Opaque Written Languagesmentioning
confidence: 99%
“…These researchers posit that strong spellers are able to differentiate between the two language systems whereas poor spellers use letter-name strategies. In a study of Afrikaans-English bilinguals (De Sousa et al, 2011), letter-name strategies were also found to be employed by students who did not notice the differences in the two orthographies. Ferroli (1991) suggests that Spanish influence in the English spelling of Spanish-English bilinguals is not related to spelling ability in Spanish, but rather to knowledge of English spelling in particular.…”
Section: Introductionmentioning
confidence: 97%
“…South African researchers (De Sousa, et al, 2011) who looked at the spelling patterns of English-Afrikaans bilinguals identified three possible explanations for negative transfer among students in their study: 1) students simply used the wrong strategy because they were unaware of the differences in the orthographies of the two languages; 2) sensitivity to sounds in the L2 caused confusion; and 3) different cognitive skills are required based on the orthographic transparency of a language. Cross-linguistic spelling/reading research has provided further evidence for the influence of relative orthographic depth of the L1 and L2, with findings that Spanish orthographic knowledge does not predict the English decoding ability of Spanish-English bilinguals (Deacon, Chen, Luo & Ramirez, 2011), whereas French orthographic knowledge does predict the English decoding ability of French-English bilinguals (Deacon, Wade-Woolley, & Kirby, 2009).…”
Section: Introductionmentioning
confidence: 99%